"Some of my Customers […] Take off Their Rolex Prior to a Client Meeting" Luxury Display at Work and the Social (Re)Construction of the Organizational Image. Issue 1 (2nd January 2022) - Schultz, Mario D.; Seele, Peter
Abstract: In this study, we follow-up on the social construction of an organizational image focusing on the role of luxury watches worn at work. In this way, we discuss the crucial role of employees' aesthetic appearance as a projector of organizational values to internal and external audiences. Drawing on the theoretical lenses of gestalt theory and the literature on aesthetics of labour, we examine the dynamics of luxury display in organizational settings via a qualitative approach, a netnography based on 193 topical entries. The netnography was guided by a pre-study conducting interviews with high level experts from the luxury watch industry. Our findings show that the display of a luxury watch at work can contribute to a harmonious organizational image. However, professional settings exist where the watch triggers an inconsistency in an employee's appearance relative to the organization that is being represented. Thus, disturbing the overall organizational image. Adopting a gestalt theoretical perspective to this social construction process, we define the "organizational gestalt ": as a dynamic projection of organizational values informed and conveyed by aesthetic, organizational representations (in this study: employees' wristwatches). We theorize that a gestalt-switch – a conversion of a previously stable organizational image – occurs when an employee's appearance projects values that conflict with the established aesthetic, organizational representations. As a consequence, the authenticity and credibility of the employee and the organization may suffer.